Holistic responses to reducing reoffending - Mahoney, Ian; Chowdhury, Rahmanara (Routledge frontiers of criminal justice, 2024)
"Offering a range of theoretical and conceptual ideas as well as practical examples, this book provides a detailed insight into holistic opportunities for promoting desistance, reducing reoffending, and supporting (re)settlement and (re)integration. Providing a fresh lens through which to view existing debates within desistance and (re)settlement literature, the book encourages different perspectives and a new framing of current approaches. To this purpose, each chapter considers what embedding a person-centered holistic approach within the criminal justice system might look like, including ways of working within the confines of current processes, potential ethical considerations, and how to maximize the potential impact to reduce reoffending. Interdisciplinary in approach, Holistic Responses to Reducing Reoffending, will appeal to students, scholars, practitioners and policymakers within criminology, criminal justice, penology, and prison studies"--